ANTIBACTERIAL ACTIVITY OF KELUAK (PANGIUM EDULE) POWDER CRUDE EXTRACT USING THE MICROWAVE ASSISTED EXTRACTION (MAE) METHOD - Freini Dessi Efendi; Eunike Debora Purba; Joni Kusnadi (Majalah Kedokteran Sriwijaya, 2020)
Keluak is commonly used by Indonesian people as a seasoning flavor. Information regarding the content of bioactive compounds and in fermented Pangi seeds (Keluak) and their activities is still little researched so that further research is needed. To extract bioactive compounds from Keluak, an extraction process is carried out using Microwave Assisted Extraction (MAE) which has the advantage of a shorter extraction time and good temperature control. The purpose of this study was to determine the use of the best material:solvent ratio and extraction time to obtain a crude extract of Keluak powder with the best antibacterial activity against Escherichia coli and Staphylococcus aureus. The experimental design used in this study was a randomized block design (RBD) which was factorial arranged with two factors, the first factor being the ratio of material:solvent (1:5 (w/v), 1:10 (w/v), and 1:15 (w/v)) and a factor of two is the extraction time (10, 15, and 20 minutes). Each treatment was repeated three times in order to obtain 27 experimental units. Data were analyzed using analysis of variance (ANOVA) with a 95% confidence interval. The best treatment in this study was the use of a material:solvent ratio of 1: 5 (w/v) and an extraction time of 15 minutes with a yield value of 87.45%, total phenol of 11.41 mg GAE / g extract, total tannins of 5.20 mg TAE/g of extract, the clear zone diameter in Escherichia coli was 5.69 mm, and the clear zone diameter in Staphylococcus aureus was 7.10 mm. The antibacterial activity of the extract on Escherichia coli and Staphylococcus aureus is only bacteriostatic so that it can only inhibit the growth of the two bacteria for a certain period of time.